Les chemins de fer atmosphériques. Première partie - Paul Smith (In Situ)
During the 1840s, as the French national railway network, centred on Paris, gradually took form, steam locomotion, for reasons of economy and security, still inspired much hesitation and criticism. This article gives an account of an alternative form of propulsion by air pressure which, in France, in England and elsewhere, provoked considerable enthusiasm, not only amongst eminent engineers, but also in scientific and administrative circles, the press and the public. It gives a brief account of the four lines exploited commercially, concentrating, in the second part of the text, on the French one, the extension of the Paris - Saint-Germain railway, which was operated atmospherically from 1847 to 1860. It tries to suggest something of the high hopes and the debates which accompanied the new system before it turned out to be a technological dead-end. Along the way, it also looks at how technical information circulated at the time, essentially back and forth across the Channel, making the experimental lines possible, and then putting an end to them.